Treatment of adults of the Valcheta Frog Pleurodema somuncurense for Chytrid fungus - Arellano, María Luz (2018)
Treatment of an ex situ colony of Valcheta frog with chloramphenicol solution was notsuccessful in eliminating chytrid fungus